MENDORONG EMPOWERMENT PEREMPUAN DI DESA SADE LOMBOK : (PENGUATAN 5TH SDG’S PROGRAM GENDER) - Wasil, Mohammad; Cahyono, Hendry; Rachmawati, Lucky; Perdini Fisabilillah, Ladi Wajuba; Nilasari, Aprillia; Hutabarat, Ruth Eviana; Hamzah , Alhafiz (LPPM Universitas Wijaya Putra, 2023)
ade Village is one of the villages in Central Lombok Regency that has preserved the customs of the Sasak tribe to this day. The low level of women's education and the importance of their role remain significant issues within the SDG’s program. This community engagement employs a problem-solving approach, directly providing education to women involved in the creative economy. Data collection techniques include direct observation, interviews, and documentation. Enhancing women's role in the creative economy, such as weaving and sales, requires specific skills. Women's empowerment in productive roles is facilitated through informal mentoring, allowing for more flexibility in learning and enhancing the Sasak women's proficiency in language use, negotiation skills, and cultural product marketing